Evaluasi Perkerasan Lentur Menggunakan Manual Desain Perkerasan Jalan 2024 dan Program Circly 7.0 - Veni Angraini Rakota; Novita Pradani (Universitas Kristen Indonesia Paulus, 2026)
Flexible pavements on highways often experience damage due to increased traffic volume and load, which impacts the service life and road maintenance costs. This study aims to evaluate the effectiveness of the 2024 Road Pavement Design Manual and CIRCLY 7.0 software in analyzing performance and predicting the remaining life of flexible pavements. The research method uses a quantitative approach with data in the form of Average Daily Traffic, road design age, vehicle growth rate, and load equivalent factor. The evaluation is carried out through manual calculations based on MDPJ 2024, including cumulative traffic load estimation and subgrade CBR analysis values, then modeled using CIRCLY 7.0 for pavement structure simulation. The analysis results show that the existing pavement thickness does not meet the MDPJ 2024 requirements with a CESA value of 0.916×10⁶ for a design life of 20 years. Based on MDPJ 2024, the recommended pavement thickness is 875 mm, while the results of the CIRCLY 7.0 analysis show that a thickness of 350 mm is still suitable for light to medium traffic..